Application of wind moment method on the design of multi-storey unbraced steel frames with partial and full strength connections - Tahir, M. M.; Shek, P. N.; Tan, C. S.; Saggaff, A. (2006)
In the multi-storey unbraced steel frame, the requirements of lateral load resistance are very critical in the design. Shear wall, core wall and bracing system are commonly applied to resist the lateral loads. However in some cases, due to the architectural requirements, the frames have to be designed as unbraced. As a result, the lateral load due to wind needs to be catered by utilizing the stiffness of connections, columns and beams. The application of wind moment method on the design of unbraced frame has becoming popular due its simplicity and straight forward approach. The objective of this paper is to compare the design of unbraced frames between partial and full strength connections with column bending on major axis. The frames were designed to satisfy the ultimate limit state and service limit state based on BS5950-1:2000. The sway-deflection of the frame was limited to hT/450 for partial strength connections and hT/300 for full strength connections, where hT is the total height of the multi-storey frame. The economic aspect was presented base on the total steel weight savings of the unbraced plane frame design using both partial and full strength connections. A parametric study on a series of two bays with two, four, six, and eight storey height were done. It was concluded that the total steel weight saving for frame design with wind moment method using full strength connection was up to 21% less than the frame design using partial strength connections.